Global Inequality in a More Educated World - Ahmed, Syud Amer (World Bank, Washington, DC, 2017)
In developing countries, younger and better-educated cohorts are entering the workforce. This developing world-led education wave is altering the skill composition of the global labor supply, and impacting income distribution, at the national and global levels. This paper analyzes how this education wave reshapes global inequality over the long run using a general-equilibrium macro-micro simulation framework that covers harmonized household surveys representing almost 90 percent of the world population. The findings under alternative assumptions suggest that global income inequality will likely decrease by 2030. This increasing educated labor force will contribute to the closing of the gap in average incomes between developing and high income countries. The forthcoming education wave would also minimize, mainly for developing countries, potential further increases of within-country inequality.